Study of regularities of distribution of macro-microstructure of ground parts (flowers, stems, leaves) chicory (Experimental biology, 2015)
In this statement describes the macro-micro elements which necessary for the human body, in the structure of terrestrial parts of chicory, class complex flowers, ground everywhere. The amount of macro and microelements in the structure of terrestrial parts of chicory (flowers, stems, leaves) defined by the method of Atomic emission digital spectrum analysis using the device «A Analyst 400», receives the results of the study. As a resultos it was found that they meet against the macro and mikrolementy potassium, sodium, magnesium, calcium, cadmium, cobalt, iron, manganese, zinc, copper.
Keywords: chicory; macro-micro elements; Phytomedicine; iron